Ocular complications in pediatric nephrotic syndrome treated with corticosteroids - L. Toruan, Yulia Margareta; Trihono, Partini Pudjihastuti; Sitorus, Rita Sita; Dwipoerwantoro, Pramita Gayatri (Indonesian Pediatric Society, 2024)
Background Posterior subcapsular cataracts (PSC) and raised intraocular pressure (IOP) are the most common ocular complications of oral steroid administration, particularly following long-term use or treatment with high doses. Objective To evaluate the association between cumulative steroid dose and duration of treatment with the occurrence of PSC and raised IOP, as well as its associated factors in children with idiopatic nephrotic syndrome (INS). Methods This cross-sectional study included children aged 4–18 years with INS who received oral steroid therapy for at least six consecutive months. Patients underwent complete eye examinations by an ophthalmologist to evaluate their visual acuity as well as the occurrence of PSC and/or raised IOP. Results Of 92 subjects, 19.6% had PSC, 12% had raised IOP, and one had a best corrected visual acuity (BCVA) of <6/20. The median cumulative steroid dose was 12,161 (range 1,795–81,398) mg and median treatment duration was 23 (range 6–84) months. There were significant positive associations between cumulative steroid dose as well as treatment duration and the occurrence of PSC, with cut-off points of 11,475 mg and 24 months, respectively, as determined by receiver operator characteristic (ROC) curves. Females were four times more likely to have PSC compared to males (PR 4; 95%CI 1.57 to 13.38; P=0.001). Cumulative steroid dose and duration of treatment were not associated with raised IOP. Conclusion Cumulative steroid dose of 11,475 mg or higher and/or duration of steroid therapy of 24 months of more were significantly associated with the occurrence of PSC, but not with raised IOP.